2020
DOI: 10.3390/electronics9122185
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis on the Effectiveness of Virtual Reality Cognitive Training (VRCT) and Computer-Based Cognitive Training (CBCT) for Individuals with Mild Cognitive Impairment (MCI)

Abstract: This meta-analysis aims to assess the effectiveness of virtual reality cognitive training (VRCT) and conventional computer-based cognitive training (CBCT) in five specific cognitive domains (i.e., global cognitive function (GCF), memory (Mem), executive function (EF), language (Lang) and visuospatial skills (VS)) of individuals with mild cognitive impairment. A total of 320 studies were yielded from five electronic databases. Eighteen randomized controlled trials met the PRISMA criteria, with 10 related to VRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
4
4
0
Order By: Relevance
“…Our review supports previous findings that suggest efficacy of VR training compared to more conventional methods in people with MCI [16][17][18][19]. Furthermore, our results are in line with previous reviews on the benefits of VR training in people with MCI regarding global cognition [15,16,18,19], but not regarding the outcomes on individual cognitive domains [16,17,19].…”
Section: Global and Domain-specific Cognitionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our review supports previous findings that suggest efficacy of VR training compared to more conventional methods in people with MCI [16][17][18][19]. Furthermore, our results are in line with previous reviews on the benefits of VR training in people with MCI regarding global cognition [15,16,18,19], but not regarding the outcomes on individual cognitive domains [16,17,19].…”
Section: Global and Domain-specific Cognitionsupporting
confidence: 92%
“…Our review supports previous findings that suggest efficacy of VR training compared to more conventional methods in people with MCI [16][17][18][19]. Furthermore, our results are in line with previous reviews on the benefits of VR training in people with MCI regarding global cognition [15,16,18,19], but not regarding the outcomes on individual cognitive domains [16,17,19]. For example, previous reviews report significant benefits of VR training on executive function [16,19] and language [17], whereas we did not identify a significant improvement in those domains.…”
Section: Global and Domain-specific Cognitionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, in our study there were positive changes had been reported after CT sessions for attention and executive function measured by pre-and post-scores of digit span forward and digit span backward, and this is aligned with the findings reported by Sarah Chui-Wai Hung et al 35 in a meta-analysis studying the effect of CCT and virtual reality training programs, that showed positive impact in attention, global cognition, and executive function.…”
Section: Several Studies Reported Positive Impact Of Ct Interventions On MCIsupporting
confidence: 92%